2004
DOI: 10.1105/tpc.020370
|View full text |Cite
|
Sign up to set email alerts
|

COS1: An Arabidopsis coronatine insensitive1 Suppressor Essential for Regulation of Jasmonate-Mediated Plant Defense and Senescence

Abstract: The Arabidopsis thaliana CORONATINE INSENSITIVE1 (COI1) gene encodes an F-box protein to assemble SCF COI1 complexes essential for response to jasmonates (JAs), which are a family of plant signaling molecules required for many essential functions, including plant defense and reproduction. To better understand the molecular basis of JA action, we screened for suppressors of coi1 and isolated a coi1 suppressor1 (cos1) mutant. The cos1 mutation restores the coi1-related phenotypes, including defects in JA sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(120 citation statements)
references
References 52 publications
6
113
0
1
Order By: Relevance
“…It encodes lumazine synthase, which catalyzes the penultimate step in riboflavin synthesis. It is suggested that AtCOS1 acts in the riboflavin pathway as a suppressor of certain JA responses, including senescence (attenuated by the SCF/COI1 complex; Xiao et al, 2004). The strong down-regulation of AtCOS1 during senescence corroborates this model.…”
Section: Jasmonic Acidsupporting
confidence: 69%
“…It encodes lumazine synthase, which catalyzes the penultimate step in riboflavin synthesis. It is suggested that AtCOS1 acts in the riboflavin pathway as a suppressor of certain JA responses, including senescence (attenuated by the SCF/COI1 complex; Xiao et al, 2004). The strong down-regulation of AtCOS1 during senescence corroborates this model.…”
Section: Jasmonic Acidsupporting
confidence: 69%
“…This suggests a threshold level of JA signaling determines fertility. This notion was also strongly supported by the findings that COI1 leaky mutant allele coi1-16 is only partially male-sterile (Xiao et al, 2004). Interestingly, JAZ proteins were shown to regulate MYB21/MYB24, the transcription factors responsible for stamen and pollen maturation.…”
Section: Ja-signaling Regulates Male Fertility Via Transcription Factsupporting
confidence: 66%
“…It is hypothesized that after activated by the JA signals, the SCF COI1 E3 ligase targets regulators of JA-signaling pathways for ubiquitination, which leads to either modification of their activity or their degradation. Two putative candidate substrates of the SCF COI1 E3 ligase have been identified recently and their functional characterization deepened our understanding of COI1-dependent plant defense signaling [55,56]. The histone deacetylase RPD3b (reduced potassium dependency 3b) was found to interact with COI1 in yeast two-hybrid screens, suggesting that it might be a COI1 target [55].…”
Section: Members Of the Ubiquitination System Are Implicated In Plantmentioning
confidence: 99%
“…Therefore, it is likely that SCF COI1 -mediated modification or breakdown of RPD3b will derepress JA-dependent gene expression. In screening for suppressors of the coi1 mutant phenotype, Xiao et al (2004) identified a mutation called cos1 (coi1 suppressor1) that can partly restore JA-related phenotype in the coi1 mutant [56]. COS1 encodes lumazine synthase, a component of the riboflavin pathway, and could be another putative target of SCF COI1 E3 ligase.…”
Section: Members Of the Ubiquitination System Are Implicated In Plantmentioning
confidence: 99%